On the affective salience of doctrines - Zahl, Simeon (Wiley, 2015)
This article builds on the work of George Lindbeck to examine the role of doctrines in the shaping of religious experience and emotion. Using a series of historical examples, it argues for the value of identifying a mode of theological argument that supports claims through attending to perceived affective effects of particular doctrines. It then applies this approach to Philipp Melanchthon’s classic articulation of the forensic model of the doctrine justification by faith in light of contemporary critiques of the doctrine as a ‘legal fiction’ to show how such critiques fail when examined from the perspective of affective salience, and draws on recent work in cognitive science to demonstrate the psychological plausibility of Melanchthon’s description of the affective consequences of justification.